Innovation policy at the regional level: the case of Wales. (19th July 2006) - Salvador, Elisa; Harding, Rebecca
This paper examines policy structures to promote innovation in Wales. Following the devolution process, the National Assembly decides its regional policy priorities and has considerable power to develop and implement policies within a range of areas, of which one is economic development. The Welsh Assembly and the Welsh Development Agency (WDA) – which play key roles in the economic development success of Wales – have a strong focus on building their region through enterprise and innovation. This paper illustrates the extent to which the strategy followed by the National Assembly and the WDA has begun to bear fruit. It critically assesses some of the published material on Welsh Development, specifically growth targets set in 'A Winning Wales', and looks at progress towards achieving these targets. This paper highlights the importance and the consequences played by the devolution process and the establishment of the Welsh Assembly in the 'catch-up' process.